Clinical And Morphological Features In Diffuse Forms Of Breast Cancer: Results Of Digital Morphometry - Yigitaliyev Alisher Bakhodir ugli; Tursunov Khasan Ziyayevich; Gafur-Okhunov Mirza-Ali Aliyarovich; Akhrayeva Dilnoza Bakhtiyarovna (Zien Journals, 2025)
In the study, tissue and cellular changes in diffuse forms of breast cancer (ductal, lobular, and inflammatory variants) were assessed using digital morphometry. Biopsy materials were scanned in the NanoZoomer system and analyzed using the QuPath and ImageJ/Image Pro Max programs. The main indicators were the proportion of stroma, excretory ducts, blood vessels, lobes, and the nuclear-cytoplasmic index (NCI). According to the results, in the ductal variant, the proportion of stroma and excretory ducts increased, the lobules shortened, and the ALS decreased to 0.69. In the lobar variant, parenchyma predominates and angiogenesis increases (LAS - 0.61), and in the inflammatory form, vascular-inflammatory changes predominate. In conclusion, digital morphometry is an effective method for differentiating diffuse phenotypes, assessing the level of cellular dedifferentiation and angiogenesis. The obtained indicators are recommended as an important prognostic criterion for making a clinical decision and determining the therapeutic orientation in breast cancer.
Keywords: breast cancer; diffuse forms; ductal invasive carcinoma